Molecular phylogeny and insular biogeography of the lowland tailorbirds of Southeast Asia (Cisticolidae: Orthotomus) - Sheldon, Frederick H.; Oliveros, Carl H.; Taylor, Sabrina S.; McKay, Bailey; Haw, Chuan Lim; Mustafa, Abdul Rahman (Elsevier Ltd, 2012)
The lowland tailorbirds of Southeast Asia (Orthotomus) offer an excellent opportunity for comparative biogeography because of their diversity in the Greater Sunda and Philippine islands. We reconstructed the phylogeny of all species in the genus using maximum likelihood, Bayesian, and coalescent methods on DNA sequences of three gene segments: an autosomal intron (TGF), a Z-linked intron (MUSK), and a mitochondrial coding gene (ND2). Although resolution is low in parts of the phylogeny, several well defined clades emerge. When considered in light of distribution, these clades indicate that the Greater Sunda and Philippine islands were occupied early in Orthotomus history by the ancestors of O. sericeus in the Greater Sundas and O. frontalis in the Philippines. Subsequently, tailorbirds diversified further in each island group: O. atrogularis, O. ruficeps, and O. sepium arose in the Greater Sundas, and O. castaneiceps castaneiceps, O. c. chloronotus, O. derbianus, O. samarensis, O. nigriceps, and O. cinereiceps in the Philippines. Among the continental taxa (including Sundaic birds), the older lineages (O. sutorius and O. sericeus) are habitat generalists and the recently evolved taxa are more specialized. In the Philippines, several taxa once considered conspecific with O. atrogularis turn out to be highly divergent species (>9% in ND2). Indeed, all Philippine allospecies are well diverged from one another. This finding supports the recent assertion of higher-than-appreciated bird endemicity in the Philippines.